THE ECOLOGICAL IMPACT OF VOLCANIC ASH DEPOSITION FROM MOUNT SEMERU’S ERUPTION ON SOIL MICROBIAL COMMUNITIES AND PLANT SUCCESSION - Robertho Kadji; Emilía Elíasdóttir; Isabella Clark (Yayasan Adra Karima Hubbi, 2025)
Volcanic eruptions are powerful geological events that drastically alter terrestrial ecosystems, yet the specific ecological recovery mechanisms, particularly the interplay between soil microbiology and vegetation, remain underexplored. The recent eruption of Mount Semeru in Indonesia deposited significant layers of volcanic ash, creating a unique natural laboratory to study primary succession. This research aimed to analyze the ecological impact of this ash deposition on the composition of soil microbial communities and the subsequent patterns of plant succession in the affected areas. The study employed a field survey method across a gradient of ash deposition thickness. Soil samples were collected for DNA metabarcoding to analyze bacterial and fungal community structures, while vegetation quadrats were established to monitor plant species recolonization and growth over a 12-month period. The results revealed a significant initial reduction in microbial diversity in heavily impacted soils, with a subsequent shift towards communities dominated by stress-tolerant, chemoautotrophic bacteria. This altered microbial landscape was strongly correlated with the emergence of pioneer plant species adapted to nutrient-poor volcanic substrates. The study concludes that volcanic ash deposition fundamentally resets soil microbial ecosystems, and this shift is a critical determining factor that directly governs the trajectory and composition of early-stage plant succession.